Reliability and Validity of the Urdu Version of Psychosomatic Symptoms Scale in Pakistani Patients - Shah, S. Mudasser; Jahangir, Muhammad; Xu, Wei; Yuan, Yonggui (Frontiers in Psychology, 2022)
The current study was aimed to assess the reliability and validity of the Urdu version of the Psychosomatic Symptoms Scale (PSSS) in Pakistani patients. The PSSS is time-saving and easy to administer. The field experts drafted the translated version of PSSS. The Urdu version of PSSS, Patient Health Questionnaire- 9 (PHQ-9), and Symptom Checklist-90 (SCL-90) Urdu version were used for assessment. The translation procedure was comprised of three steps, forward translation, back translation, and expert panel discussion. A sample of 982 (male = 50.5% and female = 49.5%) was collected with a convenient sample technique from a general hospital and private clinic. The Cronbach’s alpha for PSSS was 0.974. The confirmatory factor analysis (CFA) revealed that all the items factor loading of PSSS are more than .35, the Root Mean Square Error of Approximation (RMSEA) = 0.062, , standardized root mean residual (SRMR) = 0.043 comparative fit index (CFI) = 0.97 with confidence interval (CI) 90%. The results also showed that females (M = 72.08, SD = 6.79) are more likely to have psychosomatic symptoms than males (M = 51.21, SD = 13.36) on P <.001. The PSSS Urdu version is a useful and reliable instrument for screening, the monitoring, and the assessment of Pakistani patients’ psychosomatics symptoms